Pemanfaatan E-Learning Terhadap Prestasi Belajar Mahasiswa - Nurul Aurelia (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
problems, especially the economy in Indonesia which has deteriorated and also has an impact on the education system, so that to stop on the spread of covid-19, distant learning or home learning is implemented so that student are required to carry out online learning. The problem raised in this study is to obtain an overview of how e-learning is used of Semarang. The purpose to be achieved in this study is the use of e-learning whether it is able to generate positive or even negative behavior. This type of research was qualitative research with a case study method. Respondents in this study were students of guidance and counseling that consisted of three students and three lecturers. The data in this study were obtained through interviews, observation and documentation. Based on the results of the research data analysis shows that the use of e-learning on student learning achievement with other students is different, overall in the use of e-learning as a learning medium the highest percentage is non-linearity, feedback interactivity, just in time, multimedia-learners and last is easy accessibility. Subjects who are able to manage the use of e-learning properly will be able to show positive behavior changes in the learning properly will be able to show positive behavior changes is in the learning process, while subjects who have not been able to take advantage of e-learning show negative behavior changes in the learning process.